ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK ROTI “BAPAK BAKERY” - Septiyaningsih, Putu Mutia; Putra, G.P. Ganda; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
The aims of this research were (1) to know the variables that form factors that influence purchase decisions in Bapak Bakery, (2) to know the weight of each factor affecting purchase decisions in Bapak Bakery, and (3) to determine the variable of factor that most influence on purchasing decisions Bapak Bakery.The method of this research was survey method. Data of this research were collected  by spreading the questioner to 110 chosen respondents in all between the consumer and the final consumer. Then the questionnaire tested was processed using validity test, reability test and factor  analysis by SPSS version 22.0.  These results indicate that  the variables that form factors that influence consumer purchase decisions in Bapak Bakery, belonging to the three factors groups of factors that are considered basic. Factor 1 which included a variable taste, price, texture, location and distribution of  the product; factor 2 consist of service, expiration date, content of preservatives and nutrient content information; factors 3 consist of packaging, lawful information and advertising in the media. Weighting of each of the variables that influence consumer purchase decisions bakery products in Bapak Bakery is variable taste (0,928), price (0,915), texture (0,911), location (0,904) and distribution of the product (0.870), variable service (0,972), expiration date (0,947), content of preservatives (0,915),  and nutrient content information (0,895), variable packaging (0.925), lawful information (0.916) and advertisements in media (0.881), The factors that most influence the purchase decision is factor 1 which included a variable taste, price, texture, location and distribution of the product. Keywords: bread, purchase decision, factor analysis.
Keywords: 104